Messing with βc: A unique receptor with many goals. (April 2021) - Kan, Winnie L.; Cheung Tung Shing, Karen S.; Nero, Tracy L.; Hercus, Timothy R.; Tvorogov, Denis; Parker, Michael W.; Lopez, Angel F.
Highlights: The βc cytokines are highly pleiotropic and contribute to many normal and pathological biological processes. The structures and modes of assembly of βc cytokine receptor complexes show unique features. Organizational and dynamic properties of the βc cytokine receptor complexes control signaling outcomes. Important role for GM-CSF in hyperinflammatory immune response, or cytokine storm, seen in acutely ill COVID-19 patients. Overexpression of IL-3 receptor α-subunit is a marker and a target for therapeutic intervention in hematological diseases. Abstract: Our understanding of the biological role of the βc family of cytokines has evolved enormously since their initial identification as bone marrow colony stimulating factors in the 1960′s. It has become abundantly clear over the intervening decades that this family of cytokines has truly astonishing pleiotropic capacity, capable of regulating not only hematopoiesis but also many other normal and pathological processes such as development, inflammation, allergy and cancer. As noted in the current pandemic, βc cytokines contribute to the cytokine storm seen in acutely ill COVID-19 patients. Ongoing studies to discover how these cytokines activate their receptor are revealing insights into the fundamental mechanisms that give rise to cytokine pleiotropy and are providing tantalizing glimpses of how discrete signaling pathways may be dissected for activation with novel ligands for therapeutic benefit.